Respuesta :

Answer:

[tex]x(x^{- 10}) = x^{- 9}[/tex]

Step-by-step explanation:

We have to find the simplified form of the given expression using the exponent rule.

The expression is [tex]x(x^{- 10} )[/tex].

Now, the exponent rule says that if we multiply two terms with the same base with some constant powers then the product will have the same base and the powers will be added.

For example [tex]a^{b} \times a^{c} = a^{(b + c)}[/tex].

Here, the simplified form is  [tex]x(x^{- 10}) = x^{1} \times x^{- 10} = x^{(1 - 10)} = x^{- 9}[/tex]. (Answer)

ACCESS MORE